Notes on the behavior of opossum (Didelphis sp.) in the wild in Usumacinta Canyon, México - Luna-Jiménez, Fabiola; Botello, Francisco; Jiménez-Gómez, Ángel; Lopez-Moreno, Vicente; Romero-Gil, Juan Carlos; Belmont-Buenrostro, Francisco (Therya Notes, 2021)
Opossums are nocturnal, generalist, and opportunistic animals; however, little is known about their behavior in the wild, as most of the studies currently available have been conducted in captive individuals. This note reports the behavior of Didelphis sp. living in the wild as captured from camera trap photos and videos, highlighting the use of the tail to carry materials. The study was conducted in the Usumacinta Canyon, state of Tabasco, México. One camera trap was placed on 8 April 2020; it was left operating and set to capture photographs and videos. It was reviewed on 2 May 2020, identifying and sorting out the files corresponding to Didelphis sp. The behavior observed was identified, considering the time of capture and sex of each individual identified. A total of 209 wildlife records were obtained, with 55 pertaining to Didelphis sp.; all were captured during the night. Five main types of behavior were identified, including carrying the young on the back and transporting plant material with the tail, mostly leaves of hackberry shrub (Celtis iguanaea) to build the nest. Most of the behaviors observed correspond to foraging; however, the behavior of transporting plant material with the tail, presumably to build the nest, is reported for the first time for México. Also, three nighttime peaks of activity are reported, as well as a female carrying the young in the marsupium and later on her back.